2003
DOI: 10.1128/ec.2.2.341-350.2003
|View full text |Cite
|
Sign up to set email alerts
|

Histone H1 Is Required for Proper Regulation of Pyruvate Decarboxylase Gene Expression in Neurospora crassa

Abstract: We show that Neurospora crassa has a single histone H1 gene, hH1, which encodes a typical linker histone with highly basic N-and C-terminal tails and a central globular domain. A green fluorescent protein-tagged histone H1 chimeric protein was localized exclusively to nuclei. Mutation of hH1 by repeat-induced point mutation (RIP) did not result in detectable defects in morphology, DNA methylation, mutagen sensitivity, DNA repair, fertility, RIP, chromosome pairing, or chromosome segregation. Nevertheless, hH1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
44
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 74 publications
9
44
0
Order By: Relevance
“…Previous studies have shown that this GFP fusion allows clear visualization of ascospores, due to the strong fluorescence of the H1-GFP protein in their nuclei (27). Microscopic analysis of strains expressing the H1-GFP fusion protein confirmed the morphological differences observed in wild-type gpr-1 ϩ (N2276) and ⌬gpr-1 mutant (H1GFP) strains with regard to missing ostioles and ruptures in the perithecial wall (Fig.…”
supporting
confidence: 51%
See 2 more Smart Citations
“…Previous studies have shown that this GFP fusion allows clear visualization of ascospores, due to the strong fluorescence of the H1-GFP protein in their nuclei (27). Microscopic analysis of strains expressing the H1-GFP fusion protein confirmed the morphological differences observed in wild-type gpr-1 ϩ (N2276) and ⌬gpr-1 mutant (H1GFP) strains with regard to missing ostioles and ruptures in the perithecial wall (Fig.…”
supporting
confidence: 51%
“…Vector pMF280 contains the N. crassa histone H1 protein as a carboxyterminal GFP fusion, under the control of the ccg-1 promoter (27). Strain N2276 contains this vector targeted to the his-3 locus in an otherwise wild-type background (27).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to other fungi (403), Neurospora has only one histone H1 gene (Table 4) (242). Studies with Neurospora, S. cerevisiae, Tetrahymena, Aspergillus nidulans, and Ascobolus immersus revealed that H1 is not essential in any of these organisms (44,252,640,729,817) but, rather, is implicated in the regulation of nitrogen and carbon metabolism (242,329,727).…”
Section: Chromatin Structure and Gene Regulationmentioning
confidence: 99%
“…The his-3 targeting vector pMF272 has been used for overexpression of green fluorescent protein (GFP) fusion proteins under the control of the N. crassa ccg-1 promoter (Folco et al 2003). For overexpression of PRE-2-GFP, the entire pre-2 ORF was amplified from the G18A5 cosmid in PCRs using primers 13 and 14.…”
Section: Northern Analysismentioning
confidence: 99%